Pengaruh Kompetensi Profesional Guru Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran Fikih di MTs Salafiyah Syafi’iyah Tebuireng Jombang - Isah Munfarida; Sunardi Sunardi (LP3M IAI Al Urwatul Wutsqo Jombang, 2022)
The professional competence of teachers is very important, because professional teachers are able to create a conducive learning climate, a challenging learning atmosphere, and are able to learn in a fun way. Therefore, the professional competence of a good teacher can make students enthusiastic in learning. This study aims to determine: 1. How is the professional competence of fiqh teachers at MTs Salafiyah Syafi'iyah Tebuireng Jombang. 2. How is the student's motivation to learn in fiqh subjects at MTs Salafiyah Syafi'iyah Tebuireng Jombang 3. Is there any influence of teacher professional competence on students' motivation to learn in fiqh subjects at MTs Salafiyah Syafi'iyah Tebuireng Jombang. This research is a field research, using a quantitative approach where the data collection technique uses a questionnaire or questionnaire. For data processing using the percentage formula and a simple regression formula. The results of this study stated that the professional competence of fiqh teachers was included in the moderate category because 68% of 63 students stated the medium category, and students' learning motivation showed the medium category with a percentage of 69.8% of 63 students stated the medium category. There is a low influence of the professional competence of fiqh teachers on student learning motivation at MTs Salafiyah Syafi'iyah Tebuireng Jombang, because from computerized calculations the effect is only 6.4%.